RELEVANCE OF THE STATE DEBT POLICY OF UZBEKISTAN - Turaeva Sevara; B.I. Nurmukhamedova (KONFERENSIYALAR, 2025)
State debt policy plays a key role in ensuring macroeconomicstability and sustainable development of the economy of Uzbekistan. Public debtmanagement is an important tool for financing the budget deficit, implementinginvestment programs, and supporting vulnerable segments of the population.Public debt management in Uzbekistan is based on the key principles oftransparency, accountability and long-term sustainability. Modern approaches todebt structuring and servicing are used, aimed at minimizing risks andoptimizing the cost of borrowing.